2012
DOI: 10.1177/1753193412445160
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Italian version of the patient-rated wrist/hand evaluation questionnaire

Abstract: An Italian version of the patient-rated wrist/hand evaluation (PRWHE) questionnaire was obtained through the standardized process of cross-cultural adaptation. The PRWHE-Italian (IT) was tested on 63 patients in order to evaluate comprehension, reliability and validity as correlated to the validated version of the disabilities of the arm shoulder and hand (DASH)-IT and SF-36. No patients had difficulty completing the PRWHE-IT questionnaire. Psychometric testing demonstrated high reliability (Cronbach's alpha c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…Internal consistency is a concept that measures the extent to which items in a questionnaire are homogenous; a consistent examination will measure the same concept with similar results using multiple items. Our Cronbach's α of 0.96 demonstrated that PRWE-S achieved a good correlation between items in a scale, and our finding was correspondent with other studies [11][12][13][14][15][16][18][19][20][21][22][23]26 particularly when compared with MacDermid's reported value for the original (English) PRWE of 0.98. 31 Test-retest reliability was moderate, likely indicating that patients had changes in their status during the period between examinations, despite a short interval averaging only 10 days.…”
Section: Discussionsupporting
confidence: 91%
“…Internal consistency is a concept that measures the extent to which items in a questionnaire are homogenous; a consistent examination will measure the same concept with similar results using multiple items. Our Cronbach's α of 0.96 demonstrated that PRWE-S achieved a good correlation between items in a scale, and our finding was correspondent with other studies [11][12][13][14][15][16][18][19][20][21][22][23]26 particularly when compared with MacDermid's reported value for the original (English) PRWE of 0.98. 31 Test-retest reliability was moderate, likely indicating that patients had changes in their status during the period between examinations, despite a short interval averaging only 10 days.…”
Section: Discussionsupporting
confidence: 91%
“…The PRWHE questionnaire is used to evaluate the pain and disability level in the wrist and hand of the patient, determine treatment targets, and follow the pain and functional status after rehabilitation and surgical treatment [15]. Its reliability and validity have been tested and it has been used in various populations as it is short and easy to administer [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The most common diagnoses in patients with hand problems were hand fractures, tendon lacerations, palmar fasciectomy, or finger joint arthroplasty (metacarpophalangeal joint or proximal interphalangeal joint) [5]. The PRWHE questionnaire has been translated into Arabic, Italian, and Dutch and cross-cultural adaptation studies have been conducted [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Mean PRWHE scores are sometimes reported with one, or even two, decimal points, in effect, using a scale from 0 to 1000 or 10000. 3,10 This gives the impression that the scores are very precise. It is important to keep in mind that this is not the case.…”
Section: Resultsmentioning
confidence: 99%